Influence Of Service Quality, Water Quality And Facilities Towards Customer Satisfaction At The Regional Public Company Tirto Panguripan Drinking Water, Kendal District - Ari Prasetyani Nugroho; Mochamad Taufiq ; Marius Pramana (International Conference On Digital Advanced Tourism Management And Technology, 2023)
The results of the analysis show that hypothesis 1 (H1) that service quality has a positive effect on customer satisfaction is proven. The regression coefficient for the service quality variable has a positive sign so it can be interpreted that the higher the service quality, the higher the customer satisfaction. Hypothesis 2 (H2) that water quality has a positive effect on customer satisfaction is proven. The regression coefficient for the water quality variable has a positive sign so it can be interpreted that the better the water quality, the higher the customer satisfaction. Hypothesis 3 (H3) that facilities have a positive effect on customer satisfaction is proven. The regression coefficient for the facility variable has a positive sign, so it can be interpreted that the more adequate the facilities provided by the company, the higher the customer satisfaction.